High strength and damage resistance 2xxx series aluminum alloys
By optimizing the composition ratio and process processing of the Al-Cu-Mg-Ag-Mn-Zr system alloy, a reinforced phase is formed mainly with Ω phase, which solves the difficulty of existing aerospace aluminum alloys to have high specific strength and high damage capacity. The problem of performance limitation achieves the high strength and high damage resistance of the alloy, which is suitable for the design of next-generation aircraft.
Patent Information
- Application Number
- CN202411438302.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-10-15
AI Technical Summary
Existing aerospace aluminum alloys are difficult to have high specific strength and high damage tolerance properties.
By optimizing the composition ratio of the Al-Cu-Mg-Ag-Mn-Zr system alloy, the Cu/Mg ratio is controlled within a specific range, the formation of the S phase is reduced, and the strengthened phase is mainly composed of the Ω phase, and the impurities are applied Control of elements reduces the adverse effects of crude and insoluble compounds on damage tolerance performance.
The alloy has high strength and high damage resistance, significantly improving the material's crack propagation and damage tolerance performance, and is suitable for structural weight reduction design and long-life design of next-generation aircraft.
Smart Images

Figure CN118932231B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of 2xxx series aluminum alloys, and in particular, to a high-strength and damage-resistant 2xxx series aluminum alloy, and more specifically, to a high-strength and damage-resistant 2xxx series aluminum alloy, a preparation method thereof, and applications thereof. Background Art
[0002] With the rapid development of the aerospace industry, the comprehensive performance requirements for aircraft structural materials are becoming increasingly stringent. These requirements include excellent fatigue damage resistance, outstanding corrosion resistance, and excellent heat resistance. In this context, aluminum alloys remain one of the indispensable main structural materials in the aerospace field due to their light weight, high strength and good processing properties. In particular, Al-Cu-Mg aluminum alloys, as part of the 2xxx series, not only have high specific strength, but also show good heat resistance and high fatigue damage resistance. These characteristics make Al-Cu-Mg aluminum alloys widely used in the aerospace field. They can be processed through a variety of processes such as casting, deformation and heat treatment to meet the specific performance requirements of different components.
[0003] The 2X24 aluminum alloy series is a heat-treated aluminum alloy belonging to the Al-Cu-Mg system. It is known for its excellent room temperature tensile properties, fatigue resistance, and good pressure processing and machining properties, and can be used to manufacture various types of products. They are one of the commonly used skin materials in the aviation field. Foreign countries have successively developed 2X24 family alloys such as 2124, 2224, 2324, 2424, and 2524. Over time, the development of 2X24 family alloys has gradually evolved from the initial single static strength requirement to the comprehensive requirements of damage tolerance performance, fatigue crack growth rate, fracture toughness, and corrosion resistance. This evolution reflects the growing demand for aviation materials and the pursuit of higher performance.
[0004] In this family, 2024 aluminum alloy is widely used in military and civil aircraft due to its lower strength and good plasticity. 2524 aluminum alloy is developed on the basis of 2024 aluminum alloy by reducing the content of impurity elements iron and silicon. This improvement makes 2524 alloy show significant advantages in damage resistance, fatigue resistance and corrosion resistance, and is particularly suitable for the production of large integral components, so it is considered an ideal aircraft skin material.
[0005] The continuous progress of the aviation industry has placed increasing demands on the performance of aluminum alloy materials, especially in terms of statics, damage tolerance and corrosion resistance. In order to meet these needs, Al-Cu-Mg-Ag alloy came into being. It significantly improved the strength, heat resistance and damage tolerance of the material by adding trace amounts of silver elements on the basis of traditional Al-Cu-Mg alloy. Since the introduction of KO-1 alloy in 1962, this alloy system has undergone continuous optimization and innovation. In the 1980s, Polmear's team developed a new Al-Cu-Mg-Ag heat-resistant alloy with a yield strength of up to 520MPa based on the 2219 alloy. Subsequently, by fine-tuning the composition of the 2519 aluminum alloy, the C415 and C416 alloys were born. They have made significant progress in heat resistance, but their damage tolerance performance still needs to be improved.
[0006] In 1999, a commercial Al-Cu-Mg-Ag alloy was introduced and registered as the 2039 grade. On this basis, two new heat-resistant and damage-resistant aluminum alloys, 2040 and 2139, were introduced in 2003 and 2004 respectively. The 2040 alloy improves heat resistance by increasing the Mn content, but may sacrifice certain damage tolerance performance. The 2139 alloy improves damage tolerance performance by reducing the Mn and Mg contents, but the tensile strength drops to about 480MPa.
[0007] In 2013, in response to the pressure design requirements of the fuselage skin and pressure bulkhead of the fifth-generation advanced fighters such as F22 and F35, Alcoa developed a new Al-Cu-Mg-Ag alloy, registered as 2029 grade. While the crack growth rate of 2029-T8 aluminum plate is comparable to that of 2524 alloy, it shows excellent performance: the yield strength reaches 380MPa, the tensile strength exceeds 421MPa, and the plane stress fracture toughness exceeds 104MPa·m 1 / 2 , much higher than the level of 2524 alloy.
[0008] In order to further improve the comprehensive performance of Al-Cu-Mg-Ag alloys, in recent years, many research teams have been committed to exploring the possibility of composite microalloying of other elements with Ag elements. Shyam's research shows that adding Sc elements to Al-Cu-Mg-Ag alloys can induce in-situ phase transformation of Cu-rich phase (Al2Cu) at high temperature of 400°C. In this process, Sc atoms diffuse and occupy the interstitial sites of the Ω phase to form a new V phase (Sc2AlSi2). This new phase not only maintains high density, but also significantly enhances its thermal stability, making the alloy exhibit excellent strength and creep resistance at 400°C.
[0009] Xia Yage and others focused on the effect of Zr on the properties of Al-Cu-Mg-Ag alloy. They found that the addition of Zr can effectively refine the alloy's grains, thereby improving the alloy's mechanical properties at room temperature, including tensile strength, yield strength and elongation. However, the addition of Zr also increases the grain boundary area, resulting in more severe grain boundary sliding under high temperature and high stress conditions, thereby weakening the alloy's creep resistance.
[0010] Although rich research results have been achieved in the field of composite microalloying, most studies still focus on improving a single property of the alloy, such as strength or high temperature performance, without fully considering how to further improve the overall performance of the material through a comprehensive strengthening and toughening mechanism. Future research needs to conduct more in-depth exploration in this area to achieve a comprehensive improvement in alloy performance.
[0011] With the development of larger and longer-life aircraft, more stringent requirements are placed on the structural weight reduction and service life of new aviation aluminum alloys. Higher specific strength and higher damage tolerance performance are important directions for the development of aviation aluminum alloy materials in the future. Al-Cu-Mg-Ag alloys are considered to be important candidates for the development of aviation aluminum alloy materials in the future due to their unique properties. How to achieve the best organizational matching mode to improve the comprehensive performance of Al-Cu-Mg-Ag alloys through scientific design of major and minor elements and control of processing technology is an urgent problem to be solved for Al-Cu-Mg-Ag aluminum alloys, and it is also an urgent need for the development of the aviation field. Summary of the invention
[0012] The main purpose of the present invention is to provide a high-strength and damage-resistant 2xxx series aluminum alloy, a preparation method and application thereof, so as to solve the problem that aviation aluminum alloys in the prior art are difficult to have both high specific strength and high damage tolerance performance.
[0013] In order to achieve the above object, according to one aspect of the present invention, a high-strength and damage-resistant 2xxx series aluminum alloy is provided. In terms of weight percentage, the components of the aluminum alloy include: Cu: 4.5-5.5%, Mg: 0.5-1.2%, Mn: 0.2-0.5%, Ag: 0.65-1.2%, Fe<0.1%, Si<0.1%, Zr: 0.05-0.1%, and the balance is Al and unavoidable impurities, each unavoidable impurity is <0.05%, and the total impurities are <0.1%; wherein the weight ratio of Cu to Mg is 5-10.
[0014] Furthermore, the components of the aluminum alloy include, by weight percentage: Cu: 4.8~5.2%, Mg: 0.6~0.9%, Mn: 0.2~0.5%, Ag: 0.7~1.0%, Fe<0.1%, Si<0.1%, Zr: 0.05~0.08%, and the balance is Al and inevitable impurities, each inevitable impurity is <0.05%, and the total impurities are <0.1%; wherein, the weight ratio of Cu to Mg is 6~8.
[0015] Furthermore, the weight ratio of Ag to Mg is 1-1.5; and / or the sum of the weight percentages of Fe and Si is less than 0.15%.
[0016] Furthermore, in the 2xxx series aluminum alloy, the volume fraction of the Ω phase is 4-6%; and / or the volume fraction of the S phase is less than 1%; and / or the volume fraction of the θ phase is less than 1%; preferably, the ratio of the volume of the Ω phase to the sum of the volumes of the S phase and the θ phase is greater than 5.
[0017] According to another aspect of the present invention, a preparation method of the above-mentioned high-strength and damage-resistant 2xxx series aluminum alloy is provided, comprising the following steps: step S1, mixing, smelting, refining and casting the raw materials in sequence according to the component ratio to obtain an aluminum alloy ingot; step S2, homogenizing annealing and cooling the aluminum alloy ingot in sequence to obtain a homogenized ingot; step S3, heating and processing the homogenized ingot in sequence to obtain a processed plate; step S4, solutionizing and quenching the processed plate in sequence to obtain a quenched plate; step S5, pre-deforming and aging the quenched plate in sequence to obtain a 2xxx series aluminum alloy.
[0018] Furthermore, in step S2, the temperature of the homogenization annealing is 450-550° C., and the time is 18-22 hours.
[0019] Furthermore, in step S3, the terminal temperature of heating is 360-460° C., and the holding time is 5-10 hours; and / or the processing includes one or more of rolling, extrusion and forging.
[0020] Further, in step S4, the temperature of the solid solution is 480~540℃, and the time is 2~1200min; and / or quenching includes spray quenching and / or immersion quenching; preferably, when the quenching is spray quenching, the cooling rate of the quenching is greater than 500℃ / min; preferably, when the quenching is immersion quenching, the cooling rate of the quenching is greater than 600℃ / min.
[0021] Further, in step S5, aging includes natural aging and / or artificial aging; preferably, when the aging is natural aging, the aging time is ≥96h, and the total deformation of the pre-deformation is ≤2%; more preferably, the pre-deformation includes pre-stretching and / or straightening treatment; preferably, when the aging is artificial aging, the aging temperature is 150~250℃, the time is 5~20h, and the total deformation of the pre-deformation is 1~4%; more preferably, the pre-deformation includes pre-stretching.
[0022] According to another aspect of the present invention, an application of the above-mentioned high-strength and damage-resistant 2xxx series aluminum alloy is provided.
[0023] The present invention optimizes the ratio of main and micro alloying elements. In the Al-Cu-Mg-Ag-Mn-Zr system alloy provided, each element cooperates with each other to form a strengthening phase dominated by Ω phase. The formation of this phase enables the alloy to have both high strength and high damage resistance. In particular, the present invention reduces the formation of S phase while ensuring the formation of a large amount of dispersed Ω phase in the material by controlling the Cu / Mg ratio within a specific range, thereby achieving the optimal matching mode of the strengthening phase, thereby effectively improving the damage resistance of the material. In addition, the present invention effectively reduces the adverse effects of coarse and insoluble compounds and dispersed phases on damage tolerance performance by controlling impurity elements and other trace elements, thereby enabling 2xxx aluminum alloys to have both high strength and high damage tolerance performance, providing a material selection basis for the structural weight reduction design and long life design of the next generation of aircraft. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0025] Figure 1 The transmission electron microscope micrograph of the 2xxx series aluminum alloy of Example 1 of the present invention is shown. DETAILED DESCRIPTION
[0026] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0027] As described in the background of the present invention, there is a problem in the prior art that aviation aluminum alloys are difficult to have both high specific strength and high damage tolerance performance. In order to solve the above problems, in a typical embodiment of the present invention, a high-strength and damage-resistant 2xxx series aluminum alloy is provided. In terms of weight percentage, the components of the aluminum alloy include: Cu: 4.5~5.5%, Mg: 0.5~1.2%, Mn: 0.2~0.5%, Ag: 0.65~1.2%, Fe<0.1%, Si<0.1%, Zr: 0.05~0.1%, and the balance is Al and unavoidable impurities, each unavoidable impurity is <0.05%, and the total impurities are <0.1%; wherein the weight ratio of Cu to Mg is 5~10.
[0028] After a large number of experiments, the inventors unexpectedly found that controlling the weight percentage of Cu and Mg in the alloy and the weight ratio of the two under the above conditions can effectively inhibit the formation of S phase (Al2CuMg phase) in the alloy, thereby providing favorable conditions for the formation of a large amount of dispersed Ω phase (Al2Cu phase). In the present invention, Mg and Ag elements in the 2xxx series aluminum alloy interact with each other to form atomic clusters, so that the Ω phase obtains a nucleation advantage in the competition with the θ phase (Al2Cu phase), which can increase the proportion and precipitation effect of the Ω phase. Based on the mechanism of interaction between the Ω phase and dislocations, the damage resistance of the alloy can be improved. However, if the weight ratio of Cu to Mg is too high, it may cause the proportion of the θ phase to be too high, which may easily lead to poor strengthening and toughening effects of the material. If the ratio is too low, it may cause the proportion of the S phase to be too high, which may easily reduce the damage resistance of the material. Therefore, the present application limits the content of Cu and Mg and the weight ratio of the two to the above-mentioned specific range.
[0029] In the present invention, 0.65-1.2% of Ag element is also added. After a lot of research foundation and industrial practice, the inventor found that the addition of Ag element can effectively strengthen the organization and promote the formation of strengthening phase mainly based on Ω phase in 2xxx series aluminum alloy. The formation advantage of Ω phase is obvious within the above range. However, when the Ag content exceeds 1.2%, the overall number of Ω phase reaches the upper limit. Even if the Ag content continues to increase, the effect of improving the content of Ω phase is still limited. When the Ag content is too little, it may cause insufficient formation of Mg atomic clusters, affecting the number of nuclei of Ω phase. Therefore, the present application limits the content of Ag to within the above specific range.
[0030] In addition, trace amounts of Mn and Zr elements are added as microalloying elements in the present invention. The addition of Mn and Zr elements can refine the grains of the material, improve the comprehensive performance of the material, and is also beneficial to control the morphology and distribution of the grain boundary eutectic phase (such as θ phase, S phase, etc.) in the ingot, so as to facilitate the subsequent homogenization, solution and other heat treatment process organization control. However, if the Mn content is too high, it may cause the size and number of the Mn-containing insoluble phase to increase, thereby reducing the damage tolerance performance. If the content is too low, it is difficult to effectively refine the grains; similarly, if the Zr content is too high, it may cause the number of Zr-containing dispersed phases to increase, reducing the damage tolerance performance. If the content is too low, the effect of refining the grains is also limited. Therefore, the present application specifically limits the weight percentage of Mn to 0.2~0.5%, and the weight percentage of Zr to 0.05~0.1%.
[0031] In addition, the present invention limits the content of impurity elements such as Fe and Si. Such impurity elements can form coarse and insoluble phases (such as Al7Cu2Fe phases) during the ingot smelting process. Such insoluble phases are difficult to eliminate during the subsequent heat treatment process, which will increase the crack nucleation position of the material and shorten the spacing of crack propagation, thereby seriously affecting the damage resistance of the finished product. Therefore, the content of such impurity elements in the present invention is limited to: Fe<0.1wt%, Si<0.1wt%.
[0032] In summary, the present invention optimizes the ratio of the main microalloying elements, and in the provided Al-Cu-Mg-Ag-Mn-Zr system alloy, the elements cooperate with each other to form a strengthening phase dominated by the Ω phase, and the formation of this phase enables the alloy to have both high strength and high damage resistance. In particular, the present invention controls the Cu / Mg ratio within a specific range, while ensuring the formation of a large amount of dispersed Ω phase in the material, reducing the formation of the S phase, and achieving the optimal matching mode of the strengthening phase, thereby effectively improving the damage resistance of the material. In addition, the present invention effectively reduces the adverse effects of coarse and insoluble compounds and dispersed phases on damage tolerance performance by controlling impurity elements and other trace elements, thereby enabling 2xxx aluminum alloys to have both high strength and high damage tolerance performance.
[0033] In order to further optimize the control effect on the alloy structure, in a preferred embodiment, the components of the aluminum alloy include, by weight percentage: Cu: 4.8~5.2%, Mg: 0.6~0.9%, Mn: 0.2~0.5%, Ag: 0.7~1.0%, Fe<0.1%, Si<0.1%, Zr: 0.05~0.08%, and the balance is Al and unavoidable impurities, each unavoidable impurity is <0.05%, and the total impurities are <0.1%; wherein the weight ratio of Cu to Mg is 6~8.
[0034] In order to further inhibit the formation of S phase (Al2CuMg phase) in the alloy and increase the proportion of Ω phase (Al2Cu phase), in a preferred embodiment, the weight ratio of Ag to Mg is 1 to 1.5, preferably 1 to 1.3. In order to further reduce the content of the insoluble phase and thus more effectively improve the damage resistance of the alloy, in a preferred embodiment, the sum of the weight percentages of Fe and Si is less than 0.15%.
[0035] In a preferred embodiment, in the 2xxx aluminum alloy, the volume fraction of the Ω phase is 4-6%, preferably 5-6%; and / or the volume fraction of the S phase is less than 1%, preferably less than 0.5%; and / or the volume fraction of the θ phase is less than 1%, preferably less than 0.5%; preferably, the ratio of the volume of the Ω phase to the sum of the volumes of the S phase and the θ phase is greater than 5. The alloy under the above conditions can better combine high strength and high damage tolerance performance.
[0036] As described above, the 2xxx aluminum alloy of the specific composition of the present invention contains a rich Ω phase, which can significantly improve the damage tolerance performance of the alloy on the basis of satisfying the alloy strength. Specifically, in a preferred embodiment, the yield strength R p0.2 ≥400MPa, tensile strength R m ≥500Mpa, elongation ≥10%, plane stress fracture toughness K 1C ≥50MPa·m 1 / 2 Or plane fracture toughness Kapp ≥ 110MPa·m 1 / 2 , crack growth rate (ΔK=33MPa·m 1 / 2 )≤3×10 -3 The 2xxx aluminum alloy of the present invention has significantly improved the strength of the traditional Al-Cu-Mg alloy on the basis of excellent crack growth resistance, and provides a material selection basis for the structural weight reduction design and long life design of the next generation of aircraft.
[0037] In another typical embodiment of the present invention, a preparation method of the above-mentioned high-strength and damage-resistant 2xxx series aluminum alloy is also provided, comprising the following steps: step S1, mixing, smelting, refining and casting the raw materials in sequence according to the ratio to obtain an aluminum alloy ingot; step S2, homogenizing annealing and cooling the aluminum alloy ingot in sequence to obtain a homogenized ingot; step S3, heating and processing the homogenized ingot in sequence to obtain a processed plate; step S4, solutionizing and quenching the processed plate in sequence to obtain a quenched plate; step S5, pre-deforming and aging the quenched plate in sequence to obtain a 2xxx series aluminum alloy.
[0038] First, the raw materials are mixed, smelted, refined, and cast. This process can effectively remove the gas and impurities in the melt. Then, the obtained ingot is subjected to homogenization annealing to eliminate component segregation and homogenize each element, which is conducive to improving the performance stability of the aluminum alloy. Then, heating and processing are performed to refine the aluminum alloy grains to obtain a plate of a specific size. Secondly, the plate is solid-solutioned to dissolve the soluble phase, and then quenched to uniformly distribute the quenched structure. The quenched plate is pre-deformed to eliminate the residual stress inside the alloy, so that the alloy structure is uniform and stable. Finally, aging is performed to promote the phase change inside the alloy, improve the strength and hardness of the alloy, and obtain the above-mentioned 2xxx series aluminum alloy. The preparation method of the present invention can make each component in the 2xxx alloy of the specific composition of the present invention uniform and stable.
[0039] In a preferred embodiment, in step S2, the temperature of homogenization annealing is 450-550° C. and the time is 18-22 hours. Under the above conditions, the atomic diffusion and phase change process can be carried out more fully, and the distribution of each element is more uniform. Regarding the cooling rate, conventional parameters in the technical field can be used and are not particularly limited here.
[0040] In a preferred embodiment, in step S3, the terminal temperature of heating is 360-460°C, and the holding time is 5-10 hours. Under the above conditions, the alloy can have higher thermoplasticity, which is conducive to the smooth thermal deformation of the alloy. Too low or too high temperature may cause thermal deformation, resulting in an increased risk of processing cracking.
[0041] The processing technology of the present invention can adopt conventional processes in this technical field. After a large number of experimental studies, the inventors have optimized the parameters of each processing technology in combination with the specific components of the alloy of the present invention. In a preferred embodiment, the processing includes one or more of rolling, extrusion and forging; preferably, when the processing is rolling, the rolling includes hot rolling and cold rolling performed in sequence, the number of hot rolling passes is 10 to 15 passes, the total deformation of hot rolling is ≥50%, and the end thickness of hot rolling is 4 to 200 mm; the number of cold rolling passes is 3 to 5 passes, the total deformation of cold rolling is ≥30%, and the end thickness of cold rolling is 1 to 5 mm. Under the above conditions, through the regulation of hot deformation and cold deformation, the material can obtain a more uniform and fine grain structure, and the strength and plasticity of the alloy are more matched with the damage tolerance performance.
[0042] In a preferred embodiment, in step S4, the temperature of the solid solution is 480-540°C and the time is 2-1200 min. Under the above conditions, the soluble phase in the specific component alloy of the present invention can be fully dissolved, which is more conducive to improving the strength of the alloy. In addition, the crack propagation resistance of the alloy of the present invention can be further improved, which is more conducive to improving the damage tolerance performance of the alloy. However, if the temperature is too high, the alloy is at risk of overburning the soluble phase, resulting in the scrapping of the material; if the temperature is too low, the solute atoms may not be fully dissolved, and the effect of improving the strength and damage tolerance performance of the alloy is limited.
[0043] In order to make the quenched structure of the alloy more uniform and to further improve the strength and damage tolerance performance of the alloy, in a preferred embodiment, the quenching includes spray quenching and / or immersion quenching; preferably, when the quenching is spray quenching, the cooling rate of the quenching is >500°C / min, and the endpoint temperature is 25~40°C; preferably, when the quenching is immersion quenching, the cooling rate of the quenching is >600°C / min, and the endpoint temperature is 25~40°C.
[0044] In order to make the Ω phase precipitate more uniformly and dispersedly, and further improve the strength and damage tolerance performance of the alloy, in a preferred embodiment, in step S5, aging includes natural aging and / or artificial aging; preferably, when the aging is natural aging, the time is ≥96h, and the total deformation of the pre-deformation is ≤2%; more preferably, the pre-deformation includes pre-stretching and / or straightening treatment; preferably, when the aging is artificial aging, the aging temperature is 150~250℃, the time is 5~20h, and the total deformation of the pre-deformation is 1~4%; more preferably, the pre-deformation includes pre-stretching. The 2xxx aluminum alloy of the present invention has greatly improved the strength of the traditional Al-Cu-Mg alloy on the basis of having excellent crack growth resistance, wherein the yield strength of the artificial aging state is at least 100MPa higher than that of the 2524-T3 alloy, and the damage resistance is maintained at the same level as that of the 2524 alloy.
[0045] In order to more effectively avoid aging hardening resulting in excessive pre-deformation resistance or deformation defects, in a preferred embodiment, the pre-deformation can be carried out online or offline, wherein the time interval from the completion of quenching to the completion of pre-deformation shall not be longer than 6 hours.
[0046] In another typical embodiment of the present invention, the application of the above-mentioned high-strength and damage-resistant 2xxx aluminum alloy in the field of aerospace is also provided. The present invention uses a comprehensive strengthening and toughening mechanism to make the 2xxx aluminum alloy have both high strength and high damage tolerance performance. When the 2xxx aluminum alloy of the present invention is used in the field of aerospace, the structure of aircraft and other equipment is light and the service life is long.
[0047] Typically but not limiting, in the composition of the aluminum alloy, the weight percentage of Cu is 4.5%, 4.8%, 5%, 5.2%, 5.5% or a range consisting of any two of them; the weight percentage of Mg is 0.5%, 0.6%, 0.8%, 0.9%, 1%, 1.2% or a range consisting of any two of them; the weight ratio of Cu to Mg is 5, 6, 7, 8, 9, 10 or a range consisting of any two of them; the weight percentage of Mn is 0.2%, 0.3%, 0.4%, 0.5% or a range consisting of any two of them; the weight percentage of Ag is 0.65%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2% or a range consisting of any two of them; the weight ratio of Ag to Mg is 1, 1.1, 1.2, 1.3, 1.4, 1.5 or a range consisting of any two of them.
[0048] Typically but not limiting, the volume fraction of the Ω phase is 4%, 4.5%, 5%, 5.5%, 6%, or a range consisting of any two of these values.
[0049] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0050] Example 1
[0051] The composition ratio of 2xxx series aluminum alloy is shown in Table 1.
[0052] Step S1, according to the composition ratio of 2xxx series aluminum alloy, the raw materials are mixed, smelted and refined in sequence to remove gas and impurities, and then a flat ingot with a thickness of 400 mm and a width of 1500 mm is prepared under semi-continuous casting conditions.
[0053] Step S2, subjecting the ingot to homogenization treatment at a temperature of 500° C. and a holding time of 20 h to obtain a homogenized ingot.
[0054] Step S3, cooling the homogenized ingot to 25°C. After milling, the ingot is heated at 460°C / 10h in a heating furnace, followed by 10 passes of rough rolling with a total deformation of 95%, and then 3 passes of hot finishing rolling with a total deformation of 60%, to obtain a hot-rolled plate with a thickness of 8mm. The hot-rolled plate is cold-rolled on a cold rolling mill for 5 passes with a total deformation of 75%, to obtain a cold-rolled plate with a thickness of 2mm.
[0055] Step S4, subjecting the cold-rolled sheet to a solution treatment at 500°C for a holding time of 5 minutes, and then spray quenching to 25°C at a cooling rate of 200°C / s to obtain a quenched sheet.
[0056] Step S5, subjecting the obtained quenched plate to a 2% pre-stretching deformation, and then subjecting it to artificial aging at a temperature of 180° C. for 15 h, to obtain a 2xxx aluminum alloy in the T8 state.
[0057] The TEM organization diagram of the obtained 2xxx series aluminum alloy is shown in Figure 1 ,in, Figure 1 A in the figure is a transmission electron microscope micrograph of a 2xxx aluminum alloy under a dark field image, in which the Ω phase under the <111> band axis is marked. Figure 1 B in FIG. 1 is a transmission electron microscope micrograph of a 2xxx aluminum alloy under a dark field image, in which an S phase and a θ phase under an abnormal axis are marked. The alloy is used to manufacture aircraft in the aerospace field.
[0058] Examples 2 to 12
[0059] The only difference from Example 1 is:
[0060] The composition ratios of 2xxx series aluminum alloys are different, and the specific ratios are shown in Table 1.
[0061] Example 13
[0062] The only difference from Example 1 is:
[0063] The composition ratio of 2xxx series aluminum alloy is shown in Table 1.
[0064] Step S1, according to the composition ratio of 2xxx series aluminum alloy, the raw materials are mixed, smelted and refined in sequence to remove gas and impurities, and then a round ingot with a diameter of φ400 mm is prepared under semi-continuous casting conditions.
[0065] Step S2, subjecting the ingot to homogenization treatment at a temperature of 500° C. and a holding time of 20 h to obtain a homogenized ingot.
[0066] Step S3, cooling the homogenized ingot to 25° C. Then, after peeling and sawing, the ingot is heated in a heating furnace at 460° C. / 10 h, and then extruded into an extruded strip of 150 mm×40 mm on an extruder.
[0067] Step S4, subjecting the prepared extruded strip to a solution treatment at 480°C / 5h→500°C / 2h, and then subjecting the strip to a spray water quenching at a cooling rate of 800°C / min to obtain a quenched strip.
[0068] Step S5, pre-stretching the obtained quenched strip plate by 2%, and then artificially aging it at a temperature of 180°C for 18 hours to obtain a 2xxx series aluminum alloy, which is used to make aircraft in the aerospace field.
[0069] Examples 14 to 18
[0070] The only difference from Example 1 is:
[0071] The composition ratios of 2xxx series aluminum alloys are different, and the specific ratios are shown in Table 1.
[0072] Embodiment 19
[0073] The only difference from Example 1 is:
[0074] The preparation process parameters of 2xxx series aluminum alloys are different.
[0075] Step S1, according to the composition ratio of the 2xxx series aluminum alloy in Example 1, the raw materials are mixed, smelted, and refined in sequence to remove gas and impurities, and then a flat ingot with a thickness of 400 mm and a width of 1500 mm is prepared under semi-continuous casting conditions.
[0076] Step S2, subjecting the ingot to homogenization treatment at a temperature of 450° C. and a holding time of 22 h to obtain a homogenized ingot.
[0077] Step S3, cooling the homogenized ingot to 25°C. After milling, the ingot is heated at 360°C / 10h in a heating furnace, followed by 12 passes of rough rolling with a total deformation of 97%, and then 3 passes of hot finishing rolling with a total deformation of 60% to obtain a hot-rolled plate with a thickness of 5mm. The hot-rolled plate is cold-rolled on a cold rolling mill for 3 passes with a total deformation of 60% to obtain a cold-rolled plate with a thickness of 2mm.
[0078] Step S4, subjecting the cold-rolled sheet to a solution treatment at 480° C. for a holding time of 1200 min, and then to a spray quenching treatment at a cooling rate of 550° C. / h to obtain a quenched sheet.
[0079] Step S5, subjecting the obtained quenched plate to a 4% pre-stretching deformation, and then subjecting it to artificial aging at a temperature of 150° C. for 20 h, to obtain a 2xxx series aluminum alloy.
[0080] Embodiment 20
[0081] The only difference from Example 1 is:
[0082] The preparation process parameters of 2xxx series aluminum alloys are different.
[0083] Step S1, according to the composition ratio of the 2xxx series aluminum alloy in Example 1, the raw materials are mixed, smelted, and refined in sequence to remove gas and impurities, and then a flat ingot with a thickness of 400 mm and a width of 1500 mm is prepared under semi-continuous casting conditions.
[0084] Step S2, subjecting the ingot to homogenization treatment at a temperature of 550° C. and a holding time of 18 hours to obtain a homogenized ingot.
[0085] Step S3, cooling the homogenized ingot to 30°C. After milling, the ingot is heated at 460°C / 5h in a heating furnace, followed by 10 passes of rough rolling with a total deformation of 95%, and then 3 passes of hot finishing rolling with a total deformation of 60%, to obtain a hot-rolled plate with a thickness of 8mm. The hot-rolled plate is cold-rolled on a cold rolling mill for 3 passes with a total deformation of 62.5%, to obtain a cold-rolled plate with a thickness of 3mm.
[0086] Step S4, subjecting the cold-rolled sheet to a solution treatment at 540° C. for a holding time of 2 min, and then subjecting the cold-rolled sheet to an immersion quenching treatment at a cooling rate of 620° C. / h to obtain a quenched sheet.
[0087] Step S5, subjecting the obtained quenched plate to a 1% pre-stretching deformation, and then subjecting it to artificial aging at a temperature of 250° C. for 5 h, to obtain a 2xxx series aluminum alloy.
[0088] Comparative Examples 1 to 4
[0089] The only difference from Example 1 is:
[0090] The composition ratios of 2xxx series aluminum alloys are different, and the specific ratios are shown in Table 1.
[0091] Comparative Examples 5 to 8
[0092] The only difference from Example 13 is that:
[0093] The composition ratios of 2xxx series aluminum alloys are different, and the specific ratios are shown in Table 1.
[0094] The test results of the crystal phase volume fraction, room temperature tensile properties, fracture toughness and crack growth rate properties of the 2xxx series aluminum alloys prepared in the above examples and comparative examples are shown in Table 2.
[0095] Test method:
[0096] Volume fractions of Ω phase, S phase, and θ phase: analyzed and calculated in combination with transmission electron microscopy organization diagram.
[0097] Yield strength, tensile strength, elongation: test in accordance with GB / T228.1-2021.
[0098] Plane stress fracture toughness Kapp, crack growth rate, plane strain fracture toughness K 1C : Tested using a fatigue testing machine.
[0099] Table 1
[0100]
[0101] Table 2
[0102]
[0103] For the preparation method of 2xxx alloy plate, compared with comparative example 1, examples 1 to 12 increase the content of Ag element, increase the proportion of Ω phase in the material, and improve the strength and damage tolerance performance of the material as a whole. Compared with comparative example 2, examples 1 to 12 effectively control the grain structure characteristics by adding a trace amount of Zr element, thereby improving the damage resistance of the alloy. Compared with comparative example 3, examples 1 to 12 significantly improve the damage tolerance performance of the material by reducing the content of impurity elements such as Fe and Si. Compared with the traditional 2524 alloy shown in comparative example 4, examples 1 to 12 increase the main alloy element Cu, add Ω phase forming element Ag and match the preparation process settings, and simultaneously greatly improve the strength and damage tolerance performance of the material. Similarly, for the preparation method of extruded material of 2xxx alloy plate, the comparison effect of comparative examples 5 to 8 and examples 13 to 18 is similar to that of the above-mentioned 2xxx plate, and examples 13 to 18 obtain extruded materials with higher strength and higher damage tolerance performance.
[0104] As can be seen from the above, compared with the comparative example, the embodiments of the present invention optimize the ratio of the main microalloying elements, and in the Al-Cu-Mg-Ag-Mn-Zr system alloy provided, the elements cooperate with each other to form a strengthening phase dominated by the Ω phase, and the formation of this phase enables the alloy to have both high strength and high damage resistance. In addition, it can be seen that when all process parameters are within the preferred range of the present invention, the strength and high damage tolerance performance of the 2xxx aluminum alloy are better.
[0105] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A high-strength, damage-resistant 2xxx aluminum alloy, characterized in that: The components of the aluminum alloy include, by weight percentage: Cu: 4.5~5.5%, Mg: 0.7~0.9%, Mn: 0.2~0.5%, Ag: 0.65~0.9%, Fe<0.1%, Si<0.1%, Zr: 0.05~0.1%, the balance is Al and unavoidable impurities, each of the unavoidable impurities is less than 0.05%, and the total impurities are less than 0.1%; Among them, the weight ratio of Cu to Mg is 6~8, and the weight ratio of Ag to Mg is 1.1~1.5; The volume fraction of the Ω phase is 4-6%; the volume fraction of the S phase is less than 1%; the volume fraction of the θ phase is less than 1%; the ratio of the volume of the Ω phase to the sum of the volumes of the S phase and the θ phase is greater than 5; The preparation method of the aluminum alloy comprises the following steps: Step S1, mixing, smelting, refining and casting the raw materials in sequence according to the component ratio to obtain an aluminum alloy ingot; Step S2, subjecting the aluminum alloy ingot to homogenization annealing and cooling in sequence to obtain a homogenized ingot; Step S3, heating and processing the homogenized ingot in sequence to obtain a processed plate; Step S4, performing solution treatment and quenching on the processed plate in sequence to obtain a quenched plate; Step S5, performing pre-deformation and aging treatment on the quenched plate in sequence to obtain the 2xxx series aluminum alloy; The homogenization annealing time is 18 to 22 hours, and the heating insulation time is 5 to 10 hours.
2. The 2xxx series aluminum alloy according to claim 1, characterized in that The components of the aluminum alloy include, by weight percentage: Cu: 4.8~5.2%, Mg: 0.7~0.9%, Mn: 0.2~0.5%, Ag: 0.7~0.9%, Fe<0.1%, Si<0.1%, Zr: 0.05~0.08%, the balance is Al and inevitable impurities, each of the inevitable impurities is <0.05%, and the total impurities are <0.1%; Among them, the weight ratio of Cu to Mg is 6~8, and the weight ratio of Ag to Mg is 1.1~1.
5.
3. The 2xxx series aluminum alloy according to claim 1 or 2, characterized in that: The sum of the weight percentages of Fe and Si is less than 0.15%.
4. The 2xxx series aluminum alloy according to claim 1 or 2, characterized in that: In the step S2, the temperature of the homogenization annealing is 450-550°C.
5. The 2xxx series aluminum alloy according to claim 1 or 2, characterized in that: In the step S3, The end point temperature of the heating is 360-460°C; The processing includes one or more of rolling, extrusion and forging.
6. The 2xxx series aluminum alloy according to claim 1 or 2, characterized in that: In the step S4, The solid solution temperature is 480-540°C and the time is 2-1200 min; and / or The quenching includes spray quenching and / or immersion quenching.
7. The 2xxx series aluminum alloy according to claim 6, characterized in that: In the step S4, When the quenching is the spray quenching, the cooling rate of the quenching is >500°C / min; When the quenching is the immersion quenching, the cooling rate of the quenching is greater than 600° C. / min.
8. The 2xxx series aluminum alloy according to claim 1 or 2, characterized in that: In the step S5, The aging includes natural aging and / or artificial aging.
9. The 2xxx series aluminum alloy according to claim 8, characterized in that: In the step S5, When the aging is the natural aging, the aging time is ≥96h, and the total deformation of the pre-deformation is ≤2%; the pre-deformation includes pre-stretching and / or straightening treatment.
10. The 2xxx series aluminum alloy according to claim 8, characterized in that: In the step S5, When the aging is artificial aging, the aging temperature is 150-250° C., the time is 5-20 hours, and the total deformation of the pre-deformation is 1-4%; the pre-deformation includes pre-stretching.
11. Application of the high-strength, damage-resistant 2xxx series aluminum alloy according to any one of claims 1 to 3 in the aerospace field.
Citation Information
Patent Citations
High-fire resistance A1-Cu-Mg-Ag alloy
CN101245430A
High strength and high heat resistant aluminum alloy material and preparation method thereof
CN104711468A
Method of manufacturing aluminum alloy rolled product
CN115151665A
High-damage tolerant aluminium alloy product in particular for aerospace applications
CN1829812A